Features of calculating energy characteristics of mobile radio communication channels - Горобец, Н.Н.; Елизаренко, А.А. (Radiotekhnika, 2017)
A comparative analysis of the energy characteristics of mobile radio channels, defined according to their most common models, was carried out. Adjustment of the model parameters by the results of experimental studies in the specific conditions made it possible to provide more accurate prediction. Based on the results of experimental studies an improved statistical model was suggested for calculating the energy performance of mobile radio channels in terms of the effects of the railway infrastructure, which made it possible to optimize the design decisions on technical and economic indicators.